Direct 4D printing of hydrogels driven by structural topology - Huijun Li; Paulo Jorge Da Silva Bartolo; Kun Zhou (Virtual and Physical Prototyping)
Four-dimensional (4D) printing combines shape-morphing materials and three-dimensional (3D) printing technology, enabling efficient fabrication of complex shape-changing structures. However, 4D printing of hydrogels into structures with complex shapes suffers from poor printability, which limit their practical applications. Here, we present an efficient strategy for direct 4D printing of hydrogels, leveraging intricate structural designs and highly viscous hydrogels. This strategy facilitates programmable shape-morphing through precise control of filament spacing and orientation, resulting in gradient swelling behaviours when the structures are immersed in a Ca2+-ion solution. Our study also reveals the critical role of printability in improving shape-morphing performance. On this basis, we propose a practical solution to enhance the shape-morphing capability of hydrogels with limited inherent performance by improving their printability through the addition of viscous additives such as MC or PVA. Overall, this strategy expands the list of hydrogels suitable for 4D printing, demonstrating compatibility with both synthetic and natural hydrogels, including Alginate/Methylcellulose (ALG/MC), gelatin methacryloyl (GELMA), and ALG/polyvinyl alcohol (PVA). Various sophisticated plant-inspired shape-morphing behaviours can be achieved in 4D-printed hydrogels through precise control of structural topology. The combined strategy of employing highly viscous hydrogel with intricate structural design demonstrates vast potential for applications in biomimetic soft robotics.